Concepções e ações de profissionais da saúde para atenção em rede às mulheres em situação de violência - Arboit, Jaqueline (2016)
This research was part of the discussion of the care network to women in situations of violence. Aimed to know the conceptions and actions of primary health care services of professionals for the care network for women in situations of violence. This research was exploratory and descriptive with a qualitative approach, developed in three Strategies of Family Healthcare and a Basic Health Unit from the city Santa Maria, Rio Grande do Sul. The participants were twenty and one health professional in these locations. The data collection occurred during the months from April to July 2015, through semi-structured interviews. For assessment of the data obtained, it was used the Thematic Content Analysis proposed by Minayo. Some recommendations were followed, as fixed by the Resolution 466/2012 of the National Health Council, respecting the regulatory standards for research involving human subjects. On the total study participants, fifteen are women. As for labor characteristics and professional training of health professionals, it is emphasized that seven are Community Health Workers; and the majority of the working time is less than one year. The statements of the participants were organized into three themes: facilitating factors to identify situations of violence against women in the Primary Health Care; hindering aspects for the identification of situations of violence against women in the Primary Health Care and care network to women in situations of violence. Health professionals should understand that the health care of women victims of violence does not end in the health services, and therefore they need to be able to meet the responsibilities from the different departments that set the inter-sectoral network in order to make appropriate referrals. In this perspective, health services also become strategic for the development of actions with women in situations of violence, knowing that health professionals often are included in the enviroment in which these women live. So they need to be prepared to offer these women a qualified assistance, focusing on integrality of health actions.